Viabilidade da incorporação de resíduos vitrificados de isoladores elétricos cerâmicos no processo de obtenção de revestimentos refratários produzidos a partir de concreto sílico-aluminoso - Gomes, Lucas Bonan (My University, 2014)
With the approval of the 12.305/2010 law establishing the National Policy on Solid Waste (NPSW), all waste generated in Brazilian territory should be reduced, treated and reused within the concept of sustainable development. Electrical ceramic insulators, after its life cycle, lose their insulating functions, being necessary its replacement and statistics shows its disposal by the Brazilian energy concessionaires up to 30.000 tons every year. In this aspect, the proposal of an environmental more suitable destination is shown as an important field of study. In this work, it was proposed the technical evaluation of the incorporation of electrical ceramic waste in silico-aluminous refractory concrete for the production of refractory coatings. The electrical ceramic waste was comminuted, as well as analyzed the use of different particle sizes and the effects of heat treatment and hydraulic cures. The chemical properties of raw materials were characterized and it was determined physical properties (bulk density, apparent porosity, open pore volume and water absorption), mechanical properties (tensile and compressive strength at room temperature and diametrical compressive strength at high temperature), thermal properties (thermal conductivity in different temperatures), and morphological properties (by optical microscopy). The results did not advise the use of the refractory coatings produced for structural applications, since, with an increase of the electrical ceramic waste in the refractory concrete it was observed a significant decrease on mechanical properties. By optical micrographs, it was noticed that the shape, size and waste aggregate distribution in the ceramic matrix were responsible for the brittle-fracture of the formulations. However, the use of the produced coatings showed to be promising in applications in which the thermal insulation is required. [resumo fornecido pelo autor]
Com a aprovação da Lei 12.305/2010, que institui a Política Nacional de Resíduos Sólidos (PNRS), os resíduos gerados em território brasileiro devem ser reduzidos, tratados e reutilizados dentro do conceito de desenvolvimento sustentável. Os isoladores elétricos cerâmicos, após sua vida útil, perdem suas funções isoladoras, sendo necessária sua substituição. O descarte anual, pelas concessionárias energéticas brasileiras, atinge cerca de 30.000 toneladas. Neste aspecto, a proposição de um destino ambientalmente adequado para os mesmos mostra-se uma importante área de estudo. Neste trabalho, foi proposta a verificação da viabilidade técnica da incorporação de resíduos de isoladores elétricos cerâmicos em concreto refratário sílico-aluminoso, na produção de revestimentos refratários. Os resíduos cerâmicos foram cominuídos, assim como realizadas formulações com diferentes granulometrias sendo os efeitos da operação de queima e da cura úmida avaliados. Foram caracterizadas as propriedades químicas das matérias-primas e determinadas às propriedades físicas (densidade aparente, volume dos poros abertos e absorção de água), mecânicas (resistência à tração na flexão e à compressão à temperatura ambiente e resistência à compressão diametral à temperatura elevada), térmicas (condutividade térmica em diferentes temperaturas) e morfológicas (por microscopia óptica). Os resultados obtidos não indicaram a utilização dos revestimentos refratários produzidos para aplicações estruturais, uma vez que, com aumento da incorporação de resíduo foi observada uma considerável diminuição das propriedades mecânicas do material. Foram observadas pelas micrografias ópticas, que a forma, tamanho e distribuição dos agregados de resíduo na matriz foram responsáveis pela fratura frágil das formulações. No entanto, a utilização dos revestimentos produzidos mostrou-se promissora em aplicações em que o isolamento térmico seja requerido. [resumo fornecido pelo autor]
Keywords: Materiais - Testes; Reaproveitamento (Sobras, refugos, etc.); Material cerâmico; Materials - Testing; Recycling (Waste, etc.); Ceramic materials